Mangiferin Improves Hepatic Lipid Metabolism Mainly Through Its Metabolite-Norathyriol by Modulating SIRT-1/AMPK/SREBP-1c Signaling - Li, Jian; Liu, Mengyang; Yu, Haiyang; Wang, Wei; Han, Lifeng; Chen, Qian; Ruan, Jingya; Wen, Shaoshi; Zhang, Yi; Wang, Tao (Frontiers in Pharmacology, 2018)
Abstract Objective: Mangiferin (MGF) is a natural xanthone, with regulation effect on lipid metabolism. However, the molecular mechanism remains unclear. We purposed after oral administration, MGF is converted to its active metabolite(s), which contributes to the effects on lipid metabolism. Methods: KK-Ay mice were used to validate the effects of MGF on lipid metabolic disorders. liver biochemical indices and gene expressions were determined. MGF metabolites were isolated from MGF administrated rat urine. Mechanism studies were carried out using HepG2 cells treated by MGF and its metabolite with or without inhibitors or small interfering RNA. Western blot and immunoprecipitation methods were used to determine the lipid metabolism related gene expression. AMP/ATP ratios were measured by HPLC. AMP-activated protein kinase (AMPK) activation were identified by homogeneous time resolved fluorescence (HTRF) assays. Results: MGF significantly decreased liver triglyceride and free fatty acid levels, increased sirtuin-1 (SIRT-1) and AMPK phosphorylation in KK-Ay mice. HTRF studies indicated that MGF and its metabolites were not direct AMPK activators. Norathyriol, one of MGF's metabolite, possess stronger regulating effect on hepatic lipid metabolism than MGF. The mechanism was mediated by activation of SIRT-1, liver kinase B1, and increasing the intracellular AMP level and AMP/ATP ratio, followed by AMPK phosphorylation, lead to increased phosphorylation level of sterol regulatory element-binding protein-1c. Conclusion: These results provided new insight into the molecular mechanisms of MGF in protecting against hepatic lipid metabolic disorders via regulating SIRT-1/AMPK pathway. Norathyriol showed potential therapeutic in treatment of non-alcoholic fatty liver disease.